When reality and fantasy merged: A magical realism perspective in A Kiss for Cinderella - Rahma Fitria Nurfaizah; Elisabeth Edlin Talianingrum; Diamonda Naomi Robbani (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
A Kiss for Cinderella is a literary work whose narrative combines elements of reality and fantasy, reflecting the characteristics of magical realism. Magical realism is essential in